2006
DOI: 10.1007/s11111-006-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

Child Mortality and Environment in Developing Countries

Abstract: This paper studies child mortality and fertility in 61 developing countries including the Central Asian Republics (CARs). To control for simultaneity, an estimated value of fertility was used in the mortality equation and a final specification included only exogenous socio-economic, health and environmental variables. We confirm the importance of female literacy in explaining both fertility and mortality, and also find a measure of consumption for the poorest share of the population to be significant, while co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 62 publications
0
19
0
1
Order By: Relevance
“…Moreover, Franz and FitzRoy (2006) found in 61 developing countries that fertility rate affects child mortality significantly. This study also uses health expenditure, income distributions, and nutrition as the main determinant of child mortality.…”
Section: Health Expenditure and Child Mortalitymentioning
confidence: 99%
“…Moreover, Franz and FitzRoy (2006) found in 61 developing countries that fertility rate affects child mortality significantly. This study also uses health expenditure, income distributions, and nutrition as the main determinant of child mortality.…”
Section: Health Expenditure and Child Mortalitymentioning
confidence: 99%
“…The significance of potable safe water and sanitation for child survival has been emphasised by several studies (Franz and FitzRoy, 2006;Satterthwaite et al 1996). The proximate determinants of childhood mortality in Nigeria are closely associated with neighbourhood and household level characteristics (Iyun, 2000).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In a previous study by the authors, it was found that a significant share of child mortality in the CARs could not be explained by an expanded set of traditional determinants, such as income inequality, health care spending and fertility. 25 This study uses official, country-level statistics, which are almost certainly serious underestimates of mortality in the CARS, so the true discrepancy should be higher. In the Aral Sea Basin, 40 million of the approximately 55 million inhabitants of Central Asia are surrounded by one of the worst environmental disasters of the 20 th Century-an ongoing disaster that has wreaked social, economic, as well as ecological, havoc.…”
Section: Child Mortality In Central Asiamentioning
confidence: 99%